Non‐linear fatigue propagation of multiple cracks in an aluminium metal matrix composite (AlMMC) with silicon‐carbide fibre reinforcement. Issue 3 (1st December 2019) - Lepore, Marcello A.; Sanguigno, Luigi; Zamani, Ahmad; Berto, Filippo; Maligno, Angelo R.
Abstract: The fatigue crack growth (FCG) in a mesoscale metal matrix composite (MMC) sample has been simulated by the analyses of a 3D finite elements (FEs) model of a sample volume cell of the composite. Several FCG numerical simulations have been performed on MMC specimens made of aluminium (Al) alloy and silicon carbide (SiC). First, in the microscale, the homogenization of the single MMC unit cell has been performed in order to find the crack initiation sites. Subsequently, in the mesoscale, a tensile remote load with appropriate boundary conditions has been applied on the MMC unit volume. Simulation of FCG has been carried out using the Paris law and two non‐linear laws for small‐scale yielding (SSY), namely, the modified Kujawski‐Ellyin (KE) and UniGrow laws. Finally, the FCG rates provided by numerical simulations have been compared with each other.